DESEMPENHO AGRONÔMICO E FORRAGEIRO DE LINHAGENS S4 DE MILHO EM TOP CROSSES COM TESTADORES DE BASE GENÉTICA RESTRITA - Marcondes, Mariana Martins (2013)
It was evaluated the performance of partially inbred lines (S4) of maize, from three populations, called 29, 30 and 31, in top crosses with tester of restricted genetic base (single cross hybrids), regarding to agronomic characteristics for grain and forage production, beyond bromatologic and qualitative characteristics for silage production. For the top crosses of each population, it was performed two experiments in two different environments in Guarapuava, in the agricultural crop 2011/12. The environment 1 was conducted in the experimental area of campus CEDETEG, of UNICENTRO, characterized by the spacing of 0.80 meters between rows of crop and the environment 2 was conducted in the experimental area of Três Capões Farm, characterized by the spacing of 0.45 meters between rows of crop. The experiment was in randomized block design with three replications. Were evaluated the characteristics: male flowering (MF), seed yield (SY), plant height (PH) and ear insertion height (EH) in the top crosses of three populations in both environments and, green mass productivity (GMP), dry mass productivity (DMP), stay green (SG), ideal point cut for silage after male flowering (DAF), neutral detergent fiber (NDF), acid detergent fiber (ADF), non fiber carbohydrates plus ether extract (NFC+EE), total digestible nutrients (TDN) and relative value of the silage in top crosses the 29 and 30 populations in environment 1. Significant effect was observed for the sources of variation `genotypes` and `environments` in all characteristics evaluated, the except influence of the environment for MF in top crosses of the population 30 and SY in top crosses of the population 31. It was observed for `genotypes x environment` interaction SY in all experiments. For SY stood out in both environments the top crosses hybrids 5, 35, 42, 44, 109 and 183 (of population 29); 8, 14, 18, 22, 53, 73, 77, 91, 122, 139, 160 and 173 (of population 30) and 19, 82, 97 and 213 (of population 31). Yet, in environment 1, it was showed high SY the 11 top cross hybrid of population 30. In environment 2 stood out the 185 top cross hybrid of population 29 and 37, 50, 101 and 148 top crosses hybrids of population 30. The top crosses hybrids that showed the best characteristics for forage and silage production were 14, 76, 109, 112, 140, 154 and 183 (of population 29) and 18, 22, 50, 53, 80, 82, 88, 110, 111, 131, 140 and 149 (of population 30).